2005
DOI: 10.1038/sj.cdd.4401639
|View full text |Cite|
|
Sign up to set email alerts
|

Endogenous activation of metabotropic glutamate receptors supports the proliferation and survival of neural progenitor cells

Abstract: The use of neural progenitor cells (NPCs) is limited by the incomplete knowledge of the extracellular signals regulating their proliferation and survival. We report that cultured mouse NPCs express functional mGlu3 and mGlu5 metabotropic glutamate receptors. Pharmacological blockade of both receptors reduced NPC proliferation and survival, whereas activation of mGlu5 receptors substantially enhanced cell proliferation. Adult mice lacking mGlu5 receptors or treated with mGlu5 or mGlu3 receptor antagonists showe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
116
0
2

Year Published

2007
2007
2016
2016

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 124 publications
(124 citation statements)
references
References 47 publications
5
116
0
2
Order By: Relevance
“…Di Giorgi-Gerevini et al (2005) reported that adult mice lacking mGluR5 or treated with mGluR5 antagonists showed a dramatic reduction in the number of proliferating cells in the SVZ (Giorgi-Gerevini et al, 2005). This in vivo study shows that mGluR5 are tonically activated by ambient glutamate suggesting a local source of glutamate in the SVZ consistent with our strong immunoreactivity in SVZ astrocytes (see Fig.…”
Section: Glutamate: a Positive Regulator Of Adult Neurogenesissupporting
confidence: 75%
“…Di Giorgi-Gerevini et al (2005) reported that adult mice lacking mGluR5 or treated with mGluR5 antagonists showed a dramatic reduction in the number of proliferating cells in the SVZ (Giorgi-Gerevini et al, 2005). This in vivo study shows that mGluR5 are tonically activated by ambient glutamate suggesting a local source of glutamate in the SVZ consistent with our strong immunoreactivity in SVZ astrocytes (see Fig.…”
Section: Glutamate: a Positive Regulator Of Adult Neurogenesissupporting
confidence: 75%
“…Di Giorgi-Gerevini et al (2005) reported that adult mice lacking mGluR5 or treated with mGluR5 antagonists showed a dramatic reduction in the number of proliferating cells in the SVZ (Giorgi-Gerevini et al 2005). This in vivo study shows that mGluR5 are tonically activated by ambient glutamate suggesting a local source of glutamate in the SVZ consistent with our strong immunoreactivity in SVZ astrocytes (see Fig.…”
Section: Glutamate: a Positive Regulator Of Adult Neurogenesissupporting
confidence: 77%
“…However, the in vivo effect of glutamate on neurogenesis remains incompletely understood. Glutamate has been suggested to be beneficial for neurogenesis [22][23][24], but studies on different anatomical regions in the mammalian brain and with different experimental approaches yielded discrepant results [18]: a low dose of glutamate (50 mM) applied to mouse brain slice culture increased cell proliferation in the ventricular zone, but decreased cell proliferation in the subventricular zone [24]. However, a high dose of glutamate (300 mM) applied to brain slice culture decreased cell proliferation and survival in the ventricular zone [25].…”
Section: Introductionmentioning
confidence: 99%